Animal care and management at the National Zoo : interim report (The National Academies Press, 2004)
This interim report assesses issues related to animal management, husbandry, health, and care at the Smithsonian Institution's National Zoological Park. The report finds that there are shortcomings in care and management that are threatening the well-being of the animal collection and identifies the "most pressing" issues that should be addressed